Occupational Safety and Health Management - AHMAD , ABD RAHMAN; RUSLAN, RUMAIZAH; MOHD ADI, MOHD NAZIR (2024)
This book delves into the world of Occupational Safety and Health Management (OSH), empowering you to create that very environment. Whether you're a seasoned professional or just starting your career, understanding OSH is crucial. This book breaks down complex concepts into easy-to-understand language, focusing on the essential aspects of keeping everyone safe on the job. We'll explore the legal framework that governs workplace safety, ensuring you understand your rights and responsibilities. But OSH goes beyond following rules – it's about identifying and managing risks. This book equips you with the skills to recognize hazards, assess their potential dangers, and implement strategies to minimize them. Learning from the past is key to preventing future accidents. We'll analyze real-world scenarios, dissecting accidents to understand their causes and develop effective preventative measures. You'll also gain the knowledge to handle emergencies with confidence, ensuring your preparedness in unexpected situations. The true power of OSH lies in fostering a culture of safety. This book provides practical strategies to build a work environment where safety is a shared value, not just a set of regulations. From management to frontline workers, everyone plays a crucial role in maintaining a safe workplace. Structured for efficient learning, this book starts with the foundational concepts of OSH and gradually progresses towards practical applications. Each chapter builds upon the previous one, providing a comprehensive understanding of the field.